2016
DOI: 10.2527/jas.2015-9036
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact of using specialty feed ingredients in swine and poultry production: A life cycle assessment1

Abstract: Livestock production has a variety of environmental impacts such as greenhouse gas emissions, water pollution, acidification, and primary energy consumption. The demand for livestock products is expected to grow substantially, creating even more environmental pressure. The use of specialty feed ingredients (SFI) such as supplemented AA and phytase can reduce nutrient input into the system without compromising productivity and consequently can reduce emissions. The global change impact of using SFI in pig and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 40 publications
6
49
0
2
Order By: Relevance
“…Our results are in agreement with Kebreab et al (2016) and Monteiro et al (2017b), who also did not observe differences of CED between diets with different CP and total phosphorus levels. Kebreab et al (2016) concluded that the high non-renewable energy used during IAA production could be an area where the industrial sector could act to reduce impacts.…”
Section: Global Warming Potential and Cumulative Energy Demandsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in agreement with Kebreab et al (2016) and Monteiro et al (2017b), who also did not observe differences of CED between diets with different CP and total phosphorus levels. Kebreab et al (2016) concluded that the high non-renewable energy used during IAA production could be an area where the industrial sector could act to reduce impacts.…”
Section: Global Warming Potential and Cumulative Energy Demandsupporting
confidence: 93%
“…emissions due to the effect of land use change because of rainforest conversion in crop areas, increasing GWP of soybean meal. In this situation, replacing soybean meal by cereals and IAA seems an interesting strategy to reduce GWP impact, as shown by Kebreab et al (2016) and Monteiro et al (2016).…”
Section: Global Warming Potential and Cumulative Energy Demandmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may be associated with the fact that the authors did not consider grain production with any deforestation. Contrasted results could be obtained according to the region considered, such as those obtained by KEBREAB et al (2016) in Europe, North America and South America, and by MONTEIRO et al (2016a) in Europe and South America, since the nutritional strategies affected each pig production context differently, and the effect of AA supplementation on the GWP of pig production is highly dependent on the GWP of the protein sources.…”
Section: Nutrition and Global Warming Potentialmentioning
confidence: 67%
“…According to KEBREAB et al (2016), the addition of industrial AA and phytase to pig diets also reduced EP and AP in all the regions studied.…”
Section: Nutrition and Acidification And Eutrophication Potential Of mentioning
confidence: 99%